2020
DOI: 10.1177/2041731420956541
|View full text |Cite
|
Sign up to set email alerts
|

Porous polylactic acid scaffolds for bone regeneration: A study of additively manufactured triply periodic minimal surfaces and their osteogenic potential

Abstract: Three different triply periodic minimal surfaces (TPMS) with three levels of porosity within those of cancellous bone were investigated as potential bone scaffolds. TPMS have emerged as potential designs to resemble the complex mechanical and mass transport properties of bone. Diamond, Schwarz, and Gyroid structures were 3D printed in polylactic acid, a resorbable medical grade material. The 3D printed structures were investigated for printing feasibility, and assessed by morphometric studies. Mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…Hence, we cannot confirm previous studies for AR-M2 to be biocompatible or suitable for the use in cardiovascular tissue engineering, at least not for direct or indirect contact with cells or tissues. 23 The findings presented in this study regarding the biocompatibility of PLA are in accordance with already published data 24,25 and reveal PLA to be the more favorable material to use for biological tissue. Cell viability test revealed only a discrete and acceptable reduction of cell proliferation rate after 72 hours, which The prime goal for the DC of xenogeneic tissue is the removal of residual DNA to prevent an immune reaction or even rejection of the tissue after implantation in patients.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, we cannot confirm previous studies for AR-M2 to be biocompatible or suitable for the use in cardiovascular tissue engineering, at least not for direct or indirect contact with cells or tissues. 23 The findings presented in this study regarding the biocompatibility of PLA are in accordance with already published data 24,25 and reveal PLA to be the more favorable material to use for biological tissue. Cell viability test revealed only a discrete and acceptable reduction of cell proliferation rate after 72 hours, which The prime goal for the DC of xenogeneic tissue is the removal of residual DNA to prevent an immune reaction or even rejection of the tissue after implantation in patients.…”
Section: Discussionsupporting
confidence: 91%
“…Since skull bone has different developmental and regenerative mechanisms than long bones (Lim et al, 2013), those in vivo observations cannot be compared to the computer model predictions presented here. In vitro experiments of cellular function within gyroid scaffolds have been mainly performed to test different biomaterials or 3D printing techniques, where in general it has been reported that cells are able to penetrate and proliferate within gyroid scaffolds (Melchels et al, 2010a;Tsai et al, 2015;Ataee et al, 2019;Diez-Escudero et al, 2020;Spece et al, 2020;Chen et al, 2021;Noroozi et al, 2022). Spece et al (2020) compared cellular activity within gyroid and strut-like scaffolds in terms of ALP activity, where they showed higher ALP activity in strut-like scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…This was tested on a PLA printed scaffold with different internal pore morphologies and the seeded pre-osteoblastic line showed promising proliferation and activity. 55 Further research on the application of these technologies is expected soon. The possibilities of specific designing of the internal architecture of scaffolds to mimic the extracellular matrix of target defects in patients are encouraging.…”
Section: Craniofacial Bone Regenerationmentioning
confidence: 99%
“…This was tested on a PLA printed scaffold with different internal pore morphologies and the seeded pre-osteoblastic line showed promising proliferation and activity. 55…”
Section: Craniofacial Bone Regenerationmentioning
confidence: 99%